AB0009 IDENTIFICATION OF A NOVEL POLYMORPHISM OF ERAP1 IN A GROUP OF ITALIAN PATIENTS WITH BEHçET SYNDROME. (June 2019) - Lascaro, Nancy; Leccese, Pietro; D'angelo, Salvatore; Carbone, Teresa; Padula, Angela; Martelli, Giuseppe; Padula, Maria Carmela
Abstract : Background: The endoplasmic reticulum aminopeptidase protein 1 gene ( ERAP1 ) was associated to several human diseases, including Behçet syndrome (BS), a multisystemic disorder with unknown etiology. ERAP1 protein is involved in immune response and its role can be influenced by gene single nucleotide variations (SNVs) with an unclear mechanism [1-5]. Objectives: We aim to genotype ERAP1 whole structure searching for SNVs, in 50 consecutive BS patients and 50 sex and ethnically-matched healthy controls (HC) unrelated to each others and/or to BS patients. Methods: We used both bioinformatics and molecular methodologies. Specific primers for the coverage of all ERAP1 regions were designed using the NCBI Primer-Blast tool. Genomic DNA was extracted from whole blood and amplified using in vitro PCR. Good-quality PCR amplicons were directly sequenced using the GATC Biotech Sanger sequencing service and bioinformatically analysed using Mutation Surveyor software and NCBI-Blast Nucleotide on line similarity search tool. SNV functional impact was predicted using on line PolyPhen-2 [6], while the 3D protein prediction was obtained using 3D Protean server [7]. Results: Our study was performed recruiting an explorative cohort of BS patients from Southern Italy, a population characterized by low disease prevalence. We identified a novel heterozygous SNV at 18169 nucleotide position (NG_027839.1:g.18169A>T; HGVS nomenclature) within ERAP1 exon 3 (Fig. 1a ). It was found in 7/50 (14% of cases) of BS patients and in none of HC. The novel polymorphism was submitted and released in GenBank Database (MK252970 accession number). The SNV was a missense variation responsible for the substitution glutamate (hydrophilic amino acid) to valine (hydrophobic amino acid) at 183 position (NP_057526.3:p.Glu183Val; HGVS nomenclature) (Fig. 1b ). This is a conserved site involved in the substrate binding, due to its significant role in the anchorage of the N-terminal amine group of the peptides. Because of the different amino acid chemical features, the computational assessment of the protein structure was performed (Fig. 1c ) recognizing a change in the protein energy and stability: the SNV was associated to a more stable protein chain (ΔE: -2.022), probably affecting the enzyme conformational state change and activity, as well as the substrate binding process. The amino acid change was predicted to be damaging with maximum score when PolyPhen-2 prediction software was queried (score: 1.00) (Fig. 1d ). Conclusion: We found a SNV not previously reported in literature in a relatively small group of Italian BS patients. Our data need to be tested in a larger case-control study. In particular, the link between our SNV and the protein stability is to be validated in future functional studies. References: [1] A.L. Hanson, et al. Arthritis Rheumatol 2018.70:255. [2] E. Reeveset al. J. Immunol 2013.191:35. [3] G. Kochan, et al. Proc. Natl. Acad. Sci. USA 2011.108:7745. [4] M. Takeuchi, et al. Ann. Rheum. Dis 2016.75:2208. [5] M.J. Ombrello, et al. Curr. Opin. Rheumatol 2015.27:349. [6] I.A. Adzhubei, et al. Nat. Methods 2010.7:248. [7] T.N. Plasterer. PROTEAN. Protein sequence analysis and prediction. Mol Biotechnol 2000.16:117. Acknowledgement: Many thanks to Professor Olivieri for his "heredity" Disclosure of Interests: Nancy Lascaro: None declared, Pietro Leccese: None declared, Salvatore D'Angelo: None declared, Teresa Carbone: None declared, Angela Padula Speakers bureau: Lilly Italia EMS, Giuseppe Martelli: None declared, Maria Carmela Padula: None declared